Macrophage plasticity and polarization in tissue repair and remodelling. (29th November 2012) - Mantovani, Alberto; Biswas, Subhra K; Galdiero, Maria Rosaria; Sica, Antonio; Locati, Massimo
Abstract Mononuclear phagocyte plasticity includes the expression of functions related to the resolution of inflammation, tissue repair and remodelling, particularly when these cells are set in an M2 or an M2‐like activation mode. Macrophages are credited with an essential role in remodelling during ontogenesis. In extraembryonic life, under homeostatic conditions, the macrophage trophic and remodelling functions are recapitulated in tissues such as bone, mammary gland, decidua and placenta. In pathology, macrophages are key components of tissue repair and remodelling that occur during wound healing, allergy, parasite infection and cancer. Interaction with cells bearing stem or progenitor cell properties is likely an important component of the role of macrophages in repair and remodelling. These properties of cells of the monocyte–macrophage lineage may represent a tool and a target for therapeutic exploitation.